PENTINGNYA PERAN DOSEN DALAM PRAKTIK KEWIRAUSAHAAN MAHASISWA MANAJEMEN - Nahan, Noorjaya; Abdi, Muhamad Ruzaini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service aims to describe the importance of the role of lecturers in assisting the entrepreneurial practices of students of the Management Study Program. The problems faced by students in entrepreneurial practice include low courage to start a business, weak business planning, limited product creativity, and obstacles in marketing. The method used in this activity is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Service activities are carried out through the stages of entrepreneurship socialization, assistance in the preparation of business ideas and plans, the implementation of business practices, and monitoring and evaluation. The results of the activity show that lecturer assistance has a positive impact on increasing motivation, confidence, creativity, and managerial ability of students in running a business. Students are able to develop products, market independently, and show improvement in soft skills such as communication, teamwork, and responsibility. This activity concluded that the role of lecturers as supervisors, motivators, facilitators, and evaluators greatly determines the success of student entrepreneurial practices. Therefore, lecturer assistance in entrepreneurship practice needs to be strengthened as an applicative learning strategy in producing independent and competitive young entrepreneurs.